2015
DOI: 10.1002/jmv.24433
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chikungunya virus infection in children from India during 2009–2010: A cross sectional observational study

Abstract: Chikungunya virus, a small (about 60-70 nm diameter), spherical, enveloped, positive, single stranded RNA virus is transmitted by Aedes mosquitoes. After a short period of incubation (3-5 days) symptoms like fever with joint pains and others start appearing. After a gap of 20 years, this virus re-emerged during 2006-2008 in India causing a major outbreak of CHIKV in India. This study was conducted subsequent to the major outbreak in order to evaluate the proportion of chikungunya virus infection in children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
(30 reference statements)
2
6
1
Order By: Relevance
“…Nonetheless, studies on pediatric cases of severe chikungunya fever resulting in hospitalization are limited. In contrast to other studies 7 , differences between infants and adolescents were not determined in our study, which could be relevant because a study in India showed distinct clinical manifestations in infants and older children 8 .…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, studies on pediatric cases of severe chikungunya fever resulting in hospitalization are limited. In contrast to other studies 7 , differences between infants and adolescents were not determined in our study, which could be relevant because a study in India showed distinct clinical manifestations in infants and older children 8 .…”
contrasting
confidence: 99%
“…A vesicular-bullous rash was commonly observed, primarily in children aged <6 months but also in older patients (e.g., patient 2, aged 13 years). Unlike the adult population, pediatric patients appear to exhibit severe dermatological manifestations [6][7][8][9] . Robin et al reported that 13 children aged <6 months who were hospitalized for chikungunya fever presented with severe vesicular-bullous rash 10 .…”
mentioning
confidence: 99%
“…18 Furthermore, a multicenter study in India in the period of June 2009 to May 2010, verified significant differences in clinical manifestations (exanthema, headache, arthralgia/arthritis, vomiting and irritability) among children aged eight to 18 years, when comparing infants under the age of eight. 19 The clinical findings of this present study were fever and cutaneous manifestations (in all cases), followed by irritability, arthralgias/arthritis and vomiting, while the laboratorial tests had high frequency of anemia, alterations in the leukogram, increased cellularity in LCR and the aminotransferases. The involvement of the multisystemic chikungunya infection in infants, with predominance of the cutaneous tissue whose pathogenesis is still not well understood.…”
Section: Discussionsupporting
confidence: 55%
“…Increased transport activities supported the transmission of the virus and number of cases are getting registered due to infected travellers all over the world [15,16]. Multicentre surveillance studies are the most effective way to estimate the magnitude of the disease burden at different geographic locations and to evaluate the transmission dynamics of Chikungunya infection [1,17]. Though Chikungunya is a self-limiting disease, severe manifestations like persistent arthralgia and myalgia may increase the duration of illness [18].…”
Section: Discussionmentioning
confidence: 99%